Five Anglo-Norman motets - Evereist, Mark (Newton Abbot Antico edition)
Here are collected all the surviving motets in Anglo-Norman, the form of French spoken by the aristocracy in thirteenth-century England. Only one, Volez oyer le castoy, is an Anglo-Norman original; the others, Duce creature, Veine pleine de duur, Amor vient tout and Au queer ay un maus, are adaptations of French or Latin motets. For three solo singers, but also performable instrumentally. vi + 11 pages.